Metoder för hantering av tvärsnittskorrelation - Lindén,Tilda; Wojcieszek,Eryka (2024)
This study examines how three different methods for addressing cross-sectional dependency can affect the regression results. By ignoring the problem, using a two-way fixed effects model and using Common Correlated Effects (CCE), three regressions are run to answer the research question. In order to conduct this analysis, a growth model is specified and consists of the following explanatory variables: labour, capital, human capital, trade openness, real exchange rate and economic freedom. The panel regression consists of 53 countries spanning the time period from 1981 to 2019. Contrary to previous research, the results show no drastic changes between the three methods. There are, however, some interesting findings regarding some of the variables, but further research is needed to clarify these results.
Keywords: Cross-sectional dependence; Economic growth; CCE; Pesaran’s CD test Tvärsnittskorrelation; Ekonomisk tillväxt; Pesarans CD-test